Bounds of E-capacity Region for Multiple-access Channel With Random Parameter - Haroutunian, Mariam E. (Mathematical Problems of Computer Science, 2021)
The discrete memoryless multiple-access channel with random parameter is investigated. Various situations, when the state of the channel is known or unknown on the encoders and decoder, are considered. Some bounds of E-capacity and capacity regions for average error probability are obtained.